Proposals for a National Health Service - Great Britain. National Health Service
1946-01 1946 1940s 16 pages Remuneration of Doctors. 33. Doctors working in health centres, whole-time or part-time, will be paid a basic part salary, as part of their public income; the rest of a "sum due" to each of then calculated on a capitation rate will be pooled in the centre and divided among the doctors under something like a partnership agreement. Doctors working outside the health centres will similarly be paid a basic part-salary, the rest of their remuneration depending on a capitation rate in respect of patients on their lists. 34. All remuneration of doctors, under either system, will be fixed by national regulations and will have regard to any national standards recommended by the present Spens Committee or any subsequent body set up for the purpose. Scales of remuneration will be so arranged as to admit of extra inducement to practise in less attractive areas, probably by increase in the basic part-salary scales in areas recommended for this purpose by the Central Committee on the Distribution of Practices (below), and of extra rewards for special qualifications. Remuneration of Dentists. 35. Dentists, working - whole-time or part-time - in health centres or dental centres will be remunerated by salary, in proportion to their attendance at the centre. Supplementary arrangements will be made, while the centre system is developing, whereby dentists accepting any patient under the public service in their own surgeries can be paid on a scale of fees for approved work done. 36. All remuneration of dentists, by salary or under scales of fees, will be fixed by national regulations and will have regard to national standards recommended by a body analogous to the Spens Committee for doctors, or other body set up for the purpose. Central Committee on the Distribution of Medical Practices. 37. The Minister will set up a new central committee, working under his general directions, to supervise the distribution of medical man-power in the family doctor service. The Committee will be small and mainly professional, and will be appointed after consulting the profession, and provided with staff and offices by the Minister. /38. 292/847/4/83